Strengthening and Implementation Plan for Social Inclusion at SMA Negeri 1 Majene - Najamuddin; Kamaruddin, Syamsu A.; Ahmadin; Tamrin, Sopian; Amandaria, Riri (Indonesian Journal of Community Services, 2024)
Social inclusion has become a crucial issue to advocate for, especially in a diverse country like Indonesia, which frequently faces violence and exclusive treatment. Norms such as Pancasila and Bhinneka Tunggal Ika serve as a glue for diversity, yet tensions among citizens still exist. Schools play a strategic role in disseminating inclusive values from an early age, but challenges such as bullying, violence, and harassment persist. Therefore, it is vital to make schools arenas for practicing social inclusion, which not only fosters acceptance of differences but also addresses issues of violence. The implementation of social inclusion in schools must go beyond mere actions; it is a commitment to creating an environment that welcomes all students, regardless of background. Inclusive education helps reduce stereotypes, enhances empathy, and strengthens social skills. Schools that adopt this principle open opportunities for meaningful learning, improve emotional well-being and help shape future leaders who are sensitive to diversity. This implementation requires collaboration among teachers, students, parents, and the community, as well as support from inclusive policies. With concrete steps, social inclusion can strengthen the foundation of a more just, diverse, and equitable society.